Digital Literacy Lessons Represented in the Movie The Martian (2015) - Anggun Purnomo Arbi (Sumule Indonesia Publishing, 2025)
This research aims to describe how the 2015 film The Martian conveys and visualizes concepts related to digital literacy. This research employed a qualitative approach, utilizing content analysis, to gain a deeper understanding of how digital literacy components are represented in The Martian. Based on the results of the study, The Martian movie represents several digital literacy components, including Critical thinking and evaluation, problem-solving, functional skills, effective communication, creativity, data handling and organization, awareness of culture and society, and self-reliance. This study, which analyzes digital literacy in science fiction films, provides both theoretical and practical implications for educators and policymakers. It suggests integrating digital literacy into the curriculum using film as a teaching tool for technology and critical thinking. The researcher recommends a cross-genre analysis of films to deepen understanding of digital literacy and to use these studies by educators as teaching resources.